Optimizing of phosphate and ammonium removal from wastewater using modified zeolite: A response surface methodology approach - Nabeel, Mohammed; Dawood, Ammar Salman (Edelweiss Applied Science and Technology, 2024)
Nutrient contamination of wastewater, especially phosphate and ammonium, is a growing problem that poses major environmental and human health risks in terms of eutrophication and loss of biodiversity. Traditional methods for wastewater treatment may be highly effective, but they often come at a significant economic cost as well as environmental drawbacks. To maximize this nutrient removal these nutrients are removed using modified zeolite which is low-cost and highly effective. The Response Surface Methodology (RSM) is used in this study to enhance nutrient retention conditions, regardless of pH, contact time, and amount of adsorbent. A Central Composite Design (CCD) was then applied to study as extensively as possible the influence of these factors on this adsorption process. In important results, the alternative zeolite demonstrates 93.9% and 73% removal efficiencies for phosphate and ammonium under optimal conditions, respectively, suggesting a better performance of the modified zeolite compared to unmodified counterparts. These results highlight the promise presented by modified zeolite as a sustainable approach to enhancing current wastewater treatments in meeting or exceeding stringent environmental standards and minimizing eutrophication threats. This work is groundbreaking as it addresses large-scale nutrient pollution with a possible solution that has low cost and environmental impacts with the remedy provided by modified zeolite in wastewater treatment.